Effect of the bioregulator addition to industrial treatment on the quality of soybean (Glycine max (L.) Merr.) seeds at sixty days of conventional storage - Caiubi Pereira, Lucas; Garcia, Mayara Mariana; Braccini, Alessandro Lucca; Cavali Piana, Samara; Ferri, Gláucia Cristina; Cavalieri Matera, Thaisa; Felber, Pedro Henrique; Volpato Marteli, Danilo Cesar (Revista Colombiana de Investigaciones Agroindustriales, 2016)
Industrial seed treatment (TIS) is a well-established practice in agriculture as it ensures good seed coverage with pesticides, micronutrients, post-drying and polymers. However, there are few studies on maintaining the physiological quality of seeds when treated with plant growth regulators, particularly during conventional storage. In this context, the aim of this research was to evaluate the effect of the addition of bioregulators on the physiological quality of soybean seeds after 60 days of conventional storage. For this, an experiment was carried out in a completely randomized design with eleven treatments and four replicates. The tests carried out were germination (first and last counts), accelerated aging, seedling length (shoot, rootlet and total length), emergence velocity index in sand, final emergence percentage in sand substrate and dry biomass of the seedlings. Although the zero storage time analysis should provide better interpretation of the data, it was observed that although TIS could promote a decrease in physiological potential in soybean, all treatments exceeded the minimum germination pattern (80%), indicating that the lots were suitable for marketing in the period of up to 60 days of storage, independent of the addition of bioregulators. Para citar este artículo Pereira, L., Garcia, M., Braccini, L., Piana, S., Ferri, G., Cavalieri, T., Felber, P. & Volpato, D. (2016). Efeito da adição de biorregulador ao tratamento industrial sobre a qualidade de sementes de soja (Glycine max (L.) Merr.) aos sessenta dias de armazenamento convencional. Revista colombiana de investigaciones agroindustriales, 3(1), 15-22. DOI: http://dx.doi.org/10.23850/24220582.347